Changing Behavior Through Design: A Lab Fume Hood Closure Experiment - Aldred Cheek, Kristin; Wells, Nancy M. (Frontiers in Built Environment, 2020)
One fume hood in a laboratory can use as much energy as three homes per year. When a fume hood is in use, its door (or "sash") needs to be open, but otherwise it should be closed for safety, as well as to conserve energy. This paper examines strategies to promote fume hood closure behavior. A behavior change experiment conducted in the field tested whether a design signifier (sticker) and comparative feedback extracted from automated building and equipment data would decrease the number of times people left fume hoods open when not in use (while spaces were unoccupied or the hoods were inactive). The experiment included a control building where no fume hood intervention was implemented. The sticker and feedback together resulted in significantly fewer instances of hoods being left open (a 52.8% reduction overall). One year later, with the sticker in place and without further feedback, the instances of hoods being left open when the space was occupied but the hoods were inactive remained significantly lower than baseline. In addition to providing a low-cost strategy to bring about behavior change, findings from this study suggest opportunities to improve fume hood design and to use automated building data to provide laboratory workers with feedback to change their behavior.